Oligomeric oxidovanadium(IV) phosphates as a promising alternative to cobalt-based driers and accelerators - Foltýn, Tomáš; Matušková, Eliška; Rubeš, David; Vinklárek, Jaromír; Litecka, Miroslava; Krejčová, Anna; Honzíček, Jan (Elsevier Science BV, 2024)
This study reports promising catalytic activity of oxidovanadium(IV) dialkyl phosphates those can serve as primary driers for air-drying paints and as accelerators for room-temperature curing of unsaturated polyester resins. It describes an improved synthetic protocol giving title compounds at high yields and clarifies their molecular structure. The behavior in solution and in formulation of alkyd resin was investigated by electron paramagnetic resonance. Strong catalytic activity is documented by standard tests on several commercial alkyd binders and one multipurpose unsaturated polyester resin.
Oligomerní oxidovanadium(IV)fosfáty jako alternativa k sikativům a urychlovačům na bázi kobaltu
Keywords: Autoxidation; Vanadium; Primary drier; Alkyd resin; Unsaturated polyester; Cobalt replacement